Estudo do equilíbrio líquido-líquido em sistemas aquosos bifásicos formados por polietilenoglicol (1500, 3350 e 6000), sais de fosfato e água em diferentes temperaturas - Silva, Angélica Siqueira da (2014)
In this work, data from phase equilibrium of aqueous two-phase systems formed by polyethylene glycol (1500,3350 and 6000 ) + phosphate monobasic and dibasic ( pH 7) + water were studied . It was studied the effect of varying the temperature ( 10, 25 and 40 ° C ) and molecular weight the equilibrium data . For PEG 3350 was observed an increase of the biphasic area with decreasing temperature, showing that the formation of the aqueous two-phase systems is exothermic. To the polyethyleneglycol 1500 and 6000 was biphasic increase in area 10 and 40 °C compared to 25 °C. At all temperatures studied, the increase in molar mass contributed to the increase of the biphasic area. This fact explained by the increased hydrophobic character with increasing polyethylene glycol weight.